X-ray aspects of lung inflammation COVID-19 - R. Babić, Rade; Stanković-Babić, Gordana; Babić, Strahinja; Marjanović, Aleksandra; Govedarović, Nenad; Babić, Nevena (Medical Word, 2021)
Coronavirus disease 2019 (COVID-19) is a severe infectious disease of the respiratory system with clinical signs of severe acute respiratory syndrome. The causative agent is coronavirus 2 (SARS-CoV-2). Common symptoms of COVID-19 pneumonia are fever, cough, shortness of breath, myalgia, expectoration of sputum and sore throat. The X-ray image of COVID-19 pneumonia has its own characteristics and changes with the evolution of the disease. At the beginning of the disease, the radiological finding in the lungs may be normal or changes may be visualized in the lungs in the form of multiple hazy vaguely delineated shadows, which occur gradually, discreetly and modestly, and in the later stage confluence into larger first irregular patch formations, then they grow into a massive irregular shadow of the intensity of the frosted glass, only to diffusely cover the whole lung. Inflammatory changes are usually bilateral, less often unilateral localization, predominantly in the middle or lower lung field, on the periphery along the chest wall and / or supraphrenic. The aim of this paper is to present an X-ray image of COVID-19 pneumonia and our experiences in the X-ray diagnosis of this disease. The material of the paper consists of selected digital radiographs of the lungs and heart and CT of the lungs with pneumonia COVID-19 in 220 patients, which are during the COVID-19 pandemic from April to July 2020. were examined in covidrendgen KC Niš. The results are presented illustratively. Conclusion: The X-ray examination methods in the diagnosis of COVID-19 pneumonia are sovereign, dominant and unrivaled, and the knowledge of the authors and collaborators and the experience gained through many years of work in the profession and co-X-ray are of crucial importance.
Keywords: COVID-19 pneumonia, radiological finding, MSCT, digital radiograph of the lungs and heart